Microstructural foundations of the strength and resilience of LLDPE artificial turf yarn. Issue 43 (21st July 2016) - Ragaert, K.; Delva, L.; Van Damme, N.; Kuzmanovic, M.; Hubo, S.; Cardon, L.
ABSTRACT: The production of linear low‐density polyethylene (LLDPE) yarns for artificial turf is an advanced extrusion process, which relies heavily on the polymer's semicrystalline structure and inherent strengthening mechanisms to obtain the tailored mechanical properties so typical for turf yarns: a combination of strength and resilience. This review aims to bring together all relevant aspects in the structure–materials–processing interaction triangle which is so strongly in evidence in this application, by first summarizing the specific structural origins of the properties of the semicrystalline LLDPE and then discussing how structure evolves during the different steps of the production process, to eventually come to the final product properties of the yarn. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44080. Abstract :